STUDY OF THE RAPHANUS SATIVUS L. (SMALL RADISH) BIODIVERSITY UNDER CONDITIONS OF INTENSIVE LIGHT-CULTURE AND IDENTIFICATION OF DONORS OF ECONOMICALLY LUABLE CHARACTERS FOR BREEDING - N. G. Sinyavina; A. A. Kochetov; G. V. Mirskaya; N. A. Rushina; G. G. Panova; A. M. Artemieva (Овощи России, 2018)
Supply of the domestic fresh vegetables commodity to the population of Northern regions of Russia is one of the most priority tasks of the national economy. Lack of the local, high-quality and adopted breeding material is highly problematic for breeding programs. Generation of the new, highly productive vegetable cultivars for the glass-covered ground, including light culture, will promote to expand significantly the volume of local production of vegetables in protected ground, especially in regions with a cold climate. One of the most prospective crops for protected ground is small radish, an early ripening crop with a valuable biochemical composition. А strategy for creation of the new, highly productive forms of small radish, beard predictable complex of economically valuable characters for growing in conditions of intensive light culture, has been developed in the Agrophysical Research Institute (SaintPetersburg). At the first stage, represent interspecific set of 26 small radish cultivars from different regions, was investigated in controlled conditions (artificial light, climate cell) to reveal a complex of economically valuable properties (early maturity, productivity, morphological traits). The plants were grown in original plant grooving light equipment (lamps DNaZ-400, photoperiod 12 hours, irradiation 15-20 klk), in a small volume of substrate (peat with mineral additives). It was observed that the small radish varieties have significant diversity in precocity, productivity, resistance to bolting, also they vary in a number of morphological features of roots and leaves. Bov, Estella, Rocco (Netherlands), Nobo Chind Criollo (Peru) were the most productive cultivars. They can produce yield of commercial roots during 30 days of vegetation up to 3.5 kg/m2. In addition, cultivars – genetic resources of economically valuable properties (compact rosette, glabrous leaf, resistance to bolting) were revealed for a breeding. Parent pairs for crossing were selected. It is planned to obtain offspring small radish forms with a complex of economically valuable properties, more productive than the parents. In all matched hybrid combinations, F1 hybrids were obtained. They have a degree of hybrid superiority in roots weight from 110 to 230% over the best of the parent form. They will become the ancestors of the original forms of small radish, intended for cultivation in conditions of intense light culture.